Level awareness among employer towards SOCSO’S benefit / Raja Ainur Zanariah Raja Chik Abdullah - Raja Chik Abdullah, Raja Ainur Zanariah (2011)
The title of this study is level awareness among employers towards SOCSO benefit. SOCSO is provides social security protection to employees to reduce the sufferings and to provide financial guarantees and protection to the family. The Employees Social Security Act was first introduced in 1969 and it is applies throughout all of Malaysia in all industries including private sector. The Social Security Organization(SOCSO) has playing their role by provides protection to the injured employees and at the same time encouraging employer to provide safe and healthy working environment. Objective of this study are to seek a level awareness among employer towards SOCSO’S benefit, to determine the factor contribute most to the awareness, and to suggest an improvement in order to increase level of employer awareness. By doing this study, the tend to seek the level awareness among employer towards SOCSO ‘s benefit either they are aware or not aware. A sample of 50 respondents from a list of employer had been selected as a respondent. To obtain the information needed, the researcher will distributes a questionnaire to a respondent. Then the information will be gather and will be analyzed using a Statistical Package Social Science (SPSS) software.